Communication in asymmetric group competition over public goods - Jingjing Zhang (University of Zurich, Department of Economics, 2012)
This paper examines whether and how cheap talk communication can facilitate within-group coordination when two unequal sized groups compete for a prize that is shared equally among members of the winning group, regardless of their (costly) contributions to the group's success. We find that allowing group members to communicate before making contribution decisions improves coordination. To measure how much miscoordination remains, we employ a control treatment where miscoordination is eliminated by asking group members to reach a unanimous contribution decision. Average group contributions are not significantly different in this control treatment. Cheap talk communication thus completely solves miscoordination within groups and makes group members act as a single agent. Furthermore, it is the larger group that benefits from communication at the expense of the smaller group. Finally, content analysis of group communication reveals that after the reduction of within-group strategic uncertainty, groups reach self-enforcing agreements on how much to contribute, designate specific contributors according to a rotation scheme, and quickly discover the logic of the mixed-strategy equilibrium.
Keywords: C72; C92; D72; H41; 330; Group competition; Threshold public goods; Coordination; Cheap talk Communication; Content analysis; Experiments; Gruppenentscheidung; Öffentliche Güter; Nichtkooperatives Spiel; Test